Why has the Philippines' growth performance improved? From disappointment to promising success - Jesus Felipe; Gemma Estrada (Asian Development Bank (ADB), 2018)
This paper analyzes why the Philippines' growth performance has improved significantly in recent years. As in the medium to long term actual growth adjusts to potential, we posit that the reason behind this improvement is that the country's potential growth is increasing. We derive an estimate of the potential growth rate, defined as the growth consistent with a constant unemployment rate, through the notion of Harrod's natural growth rate and Okun's Law. Kalman filter estimation allows us to obtain a time series of potential growth rate for 1957-2017. Results corroborate that potential growth is increasing. It reached 6.3% in 2017, the highest value during the last 60 years. We find that in recent years, labor productivity growth (technical progress) accounts for most of the country's potential growth rate, as the trend labor force growth displays a downward trend. A decomposition of labor productivity growth shows that the within effect accounts for 70% of it, and that most of it is due to manufacturing productivity growth. As actual growth in 2017 reached 6.7% and to maintain the growth momentum, Philippine authorities ought to focus on increasing potential growth to enable more room for growth in a stable macroeconomic environment. Finally, two key results emerge from our analysis of output and productivity growth, and employment. First, estimates of Okun's Law indicate that the response of Philippine unemployment and visible underemployment to output growth is very small. However, the response of total underemployment is positive and significant. Second, productivity growth does not destroy employment.
Keywords: E24; E32; O47; O53; 330; Harrod's natural growth rate; Kalman filter; Okun's Law; Philippines; potential growth; underemployment; unemployment